2010
DOI: 10.1093/glycob/cwq201
|View full text |Cite
|
Sign up to set email alerts
|

Delta inulin: a novel, immunologically active, stable packing structure comprising  -D-[2 -> 1] poly(fructo-furanosyl)  -D-glucose polymers

Abstract: We report a novel isoform of β-D-[2 → 1] poly(fructo-furanosyl) α-D-glucose termed delta inulin (DI), comparing it with previously described alpha (AI), beta (BI) and gamma (GI) isoforms. In vitro, DI is the most immunologically active weight/weight in human complement activation and in binding to monocytes and regulating their chemokine production and cell surface protein expression. In vivo, this translates into potent immune adjuvant activity, enhancing humoral and cellular responses against co-administered… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
100
0
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 112 publications
(106 citation statements)
references
References 32 publications
(38 reference statements)
5
100
0
1
Order By: Relevance
“…Taken together, these findings may indicate that the increased expression of VT observed in the present study, may protect the piglet organism against excessive cytolytic action of activated complement. The studies of Cooper (1995) and Cooper and Petrovsky (2011) clearly indicate that γ and δ inulin have the ability to activate the alternative complement pathway via activation of the complement C3 receptors localised on the surface of macrophages.…”
Section: Discussionmentioning
confidence: 99%
“…Taken together, these findings may indicate that the increased expression of VT observed in the present study, may protect the piglet organism against excessive cytolytic action of activated complement. The studies of Cooper (1995) and Cooper and Petrovsky (2011) clearly indicate that γ and δ inulin have the ability to activate the alternative complement pathway via activation of the complement C3 receptors localised on the surface of macrophages.…”
Section: Discussionmentioning
confidence: 99%
“…Advax adjuvant is based on immunologically active delta inulin microparticles (21) and has proved successful in both animal studies and human vaccine trials (22). In preclinical models, Advax was shown to enhance the immunogenicity of a broad range of viral vaccines, including pandemic influenza virus (23), HIV (24), hepatitis B virus (25), African horse sickness virus (26), and JEV (18,27).…”
mentioning
confidence: 99%
“…However, JE-VAX remains the "gold standard" for immunogenicity and safety comparisons of new-generation vaccines against JE (8). Using JE-VAX as a comparator, we showed that JE-ADVAX, a Vero cell culture-grown inactivated JEV antigen (ccJE) (9), combined with Advax, a novel polysaccharide adjuvant derived from delta inulin (10), provided immunogenicity greatly superior to that of JE-VAX in mice and horses (11). In the same study, we also found that JE-ADVAX elicited levels of neutralizing antibody against serologically related flaviviruses of medical significance (West Nile and Murray Valley encephalitis viruses) that were indicative of cross-protective immunity, because they exceeded the titers against the homologous virus (JEV) generated by immunization with the gold standard JE-VAX (11).…”
mentioning
confidence: 99%